Response of cotton genotypes to the incidence of Alternaria leaf spot - Cia,Edivaldo (2016)
ABSTRACT In field experiments and under natural occurrence of the pathogen, 18 cotton genotypes, comprising cultivars and lineages, were evaluated for their reaction to Alternaria leaf spot caused by Alternaria macrospora Zimm. High genetic diversity of resistance to the pathogen was observed, and four groups of reaction to the disease were detected in the environment where the disease showed greater intensity. Differences in the phenotypic stability of resistance were also found, and there were stable genotypes, i.e. of expected performance, both in the resistant and in the susceptible material. It must be emphasized that the existence of unstable genotypes of inconsistent performance, according to the intensity of the disease occurrence, can lead to errors with respect to their resistance degree.